Immune marker expression of irradiated mesothelioma cell lines - Chang, Faith; Keam, Synat; Hoang, Tracy Seymour; Creaney, Jenette; Gill, Suki; Nowak, Anna K.; Ebert, Martin; Cook, Alistair M. (Frontiers in Oncology, 2022)
Background: Though immune checkpoint inhibition has recently shown encouraging clinical efficacy in mesothelioma, most patients do not respond. Combining immune checkpoint inhibition with radiotherapy presents an attractive option for improving treatment responses owing to the various immunomodulatory effects of radiation on tumors. However, the ideal dosing and scheduling of combined treatment remains elusive, as it is poorly studied in mesothelioma. The present study characterises the dose- and time-dependent changes to expression of various immune markers and cytokines important to antitumor responses following irradiation of mesothelioma cell lines. Methods: Two murine (AB1, AE17) and two human (BYE, JU77) mesothelioma cell lines were treated with titrated gamma-radiation doses (1-8 Gy) and the expression of MHC class-I, MHC class-II and PD-L1 was measured over a series of post-irradiation timepoints (1-72 hours) by flow cytometry. Levels of cytokines IL-1α, IL-1β, IL-6, IL-10, IL-12p70, IL-17A, IL-23, IL-27, MCP-1, IFN β, IFN-γ, TNF-α, and GM-CSF were measured by multiplex immunoassay in murine cell lines following 8 Gy radiation. Results: Following irradiation, a dose-dependent upregulation of MHC-I and PD L1 was observed on three of the four cell lines studied to varying extents. For all cell lines, the increase in marker expression was most pronounced 72 hours after radiation. At this timepoint, increases in levels of cytokines IFN β, MCP-1 and IL-6 were observed following irradiation with 8 Gy in AB1 but not AE17, reflecting patterns in marker expression. Conclusions: Overall, this study establishes the dose- and time-dependent changes in immune marker expression of commonly studied mesothelioma cell lines following radiation and will inform future study into optimal dosing and scheduling of combined radiotherapy and immune checkpoint inhibition for mesothelioma.